Comparison of the Growth of Six Eucalyptus Species in Angola - Cristobal Delgado-Matas; Timo Pukkala (International Journal of Forestry Research)
Eucalyptus species have been planted in Angola since the early twentieth century. The species introduction experiment of Tchianga, in the Angolan Highlands, was established in 1966/1967. The experiment included several tropical pines and eucalypts. The plots were 43 years old when measured in 2009. Species included Eucalyptus saligna Sm., E. camaldulensis Dehnh., E. macarthurii H. Deane & Maiden, E. resinifera Sm., E. siderophloia Benth., and E. grandis Hill ex. Maiden. E. saligna had the highest stand volume at 43 years (1427 m3 ha−1), followed by E. grandis (1006 m3 ha−1). E. macarthurii and E. camaldulensis had the lowest stand volume (423 and 511 m3 ha−1, resp.). Using X-ray analyses of increment cores, it was possible to study the temporal development of the stand characteristics. An analysis of the mean annual increment showed that the optimal rotation length for most of the studied eucalypts is around 22 years with the exception of E. resinifera, for which 12–15 years is the best. E. saligna had the highest maximum mean annual increment (MMAI) of 37 m3 ha−1 attained at 22 years of age. E. grandis reached its MMAI of 25 m3 ha−1 at 28 years. The results suggest that E. saligna is the most recommended Eucalyptus species for new plantations in Angola.